2023
DOI: 10.3389/fendo.2023.1133000
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and thyroid diseases

Abstract: Selenium, a non-metallic element, is a micronutrient essential for the biosynthesis of selenoproteins containing selenocysteine. In adults, the thyroid contains the highest amount of selenium per gram of tissue. Most known selenoproteins, such as glutathione peroxidase, are expressed in the thyroid and are involved in thyroid hormone metabolism, redox state regulation, and maintenance of cellular homeostasis. Some clinical studies have shown that lack of selenium will increase the prevalence of several kinds o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 115 publications
0
7
0
1
Order By: Relevance
“…The effect of selenium may be mediated, at least in part, through inflammatory pathways. Thus, selenium supplementation seems to upregulate activated T cells ( 44 ) and to inhibit the release of several pro-inflammatory cytokines, including interleukin 2, interferon gamma (IFNγ), and tumor necrosis factor ( 2 , 45 ). A recent study found that 100 μg daily selenium supplementation in 29 women with AIT reduced IFNγ and increased interleukin 1β concentrations ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of selenium may be mediated, at least in part, through inflammatory pathways. Thus, selenium supplementation seems to upregulate activated T cells ( 44 ) and to inhibit the release of several pro-inflammatory cytokines, including interleukin 2, interferon gamma (IFNγ), and tumor necrosis factor ( 2 , 45 ). A recent study found that 100 μg daily selenium supplementation in 29 women with AIT reduced IFNγ and increased interleukin 1β concentrations ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars have reported that iodine, selenium, iron, and sex hormones all contribute to the risk of thyroid disease. Wang has indicated that a de ciency in selenium is a risk factor for various thyroid diseases [17]. Environmental factors also signi cantly contribute to autoimmune thyroid disease, with associations found between GD and smoking, excess iodine, selenium and vitamin D de ciencies, and occupational exposure to Agent Orange.…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione peroxidase plays a crucial role in safeguarding the thyroid gland against the detrimental effects of hydrogen peroxide ( 106 ). Se is an important component of antioxidant defences, and Se deficiency may exacerbate the damage caused by iodine deficiency to the thyroid ( 107 ). Iodothyronine deiodinase can initiate or terminate thyroid hormone activity, dynamically regulating thyroid hormone signal transduction ( 108 ).…”
Section: Mechanism Underlying the Interaction Between Se And Iodine I...mentioning
confidence: 99%